THE RELATIONSHIP BETWEEN ACUTE ARTERIAL OCCLUSIONS AND THE STAGE OF PERIPHERAL ARTERIAL DISEASE ACCORDING TO THE FONTAINE CLASSIFICATION - Ozguler, Ibrahim Murat; Ustunel, Latif; Uysal, Ayhan (Gunes Kitabevi Ltd Sti, 2019)
Introduction: Peripheral vascular disease is defined as narrowing of blood vessels that restricts blood flow. Atherosclerosis is the most common etiology followed by vasculitis, dysplastic syndromes, degenerative diseases, thrombosis, and thromboembolism. The mortality rate at diagnosis is 4%-6%. Atherosclerotic peripheral vascular disease and leg amputation from such condition increase the mortality rate to 30%, and the 5-year survival rate is less than 30%. Thus, disease severity and extent of peripheral vascular disease must be evaluated and presented. Materials and Method: Between January 2005 and March 2018,98 patients underwent surgery for acute arterial occlusion owing to chronic peripheral arterial disease were evaluated according to the Fontaine Classification, demographic characteristics, concomitant disease, physical examination findings, type of surgery and amputation and mortality rates, and its causes were analyzed. Results: None of the patients (n=98) presented with Fontaine stage I disease. Because peripheral arterial disease is usually observed in the elderly population, elderly patients with several health problems at advanced age are more likely to undergo extremity amputation. It can be reduced by including the ankle brachial index examination in any outpatient clinic. Other stages of the disease were also evaluated in detail. Conclusion: ABI examination should be included in the systemic examination for patients aged>70 years. Currently, lumbar hernia, osteoporosis or osteoarthritis are also observed in such patients, and the clinical signs of peripheral arterial disease are masked. Due to these diseases, the diagnosis of peripheral arterial disease is delayed.
Akut arterıyel tikanikliklar ve perıferık arter hastaliğinin fontaıne siniflamasi’na göre evresı arasindakı ılışkı
Keywords: Peripheral arterial disease; Ankle Brachial Index; Amputation